Systematization of the effects that arise in connection with the expansion of transnational bank capital - TKACHENKO, Natalia; MOMOT, Olexander (Scientific journal «World of Finance», 2019)
Introduction. Openness to transnational financial flows is one of the most important indicators of the development of banking systems. The advocates of openness of banking systems for the entry of transnational banks as positive characteristics indicate increased competition in the banking sector, increased financial stability and efficiency, application of the newest management methods, diffusion of banking innovations, consolidation of both prudential standards and standards of regulation and supervision of banking activities. The purpose.The purpose of the article is to study the signs of globalization of financial space and the main forms of the presence of foreign banks in the territory of the host country and identify a set of risks and effects arising from the expansion of transnational bank capital.Results. The main consequences of the openness of banking systems for the expansion of transnational bank capital are investigated in the article. The main forms of the presence of foreign banks in the territory of the host country are identified, namely: representation of a foreign bank, a branch of a foreign bank, a bank with foreign participation and a subsidiary bank. The factors influencing the choice by a transnational bank of a certain organizational form of presence in foreign markets are determined. The differences in the behavior of branches of transnational banks and subsidiary banks in the financial markets of the host country are examined. A set of risks emerged in the case of the openness of the banking system and the presence of branches of transnational banks is identified. A set of effects generated by the expansion of transnational bank capital is investigated.Conclusions. The removal of barriers to capital flows must be coordinated with certain measures in macroeconomic policy. Failure to comply with this condition can lead to crisis phenomena, growth of external debt, especially short-term, and threaten the financial stability of the state.